Sticky feet: a tribological study of climbing shoe rubber - Elkington, R. J.; Armitage, J. L.; Khan, T.; Bryant, M. G. (Sports Engineering, 2024)
This study examines the tribological properties of climbing shoe rubbers, challenging the common belief in the climbing community that softer rubbers are inherently grippier. This study investigates the mechanical and wear characteristics of climbing shoe rubbers by employing a high-precision modular mechanical testing environment (Bruker UMT TriboLab) and representative granite counter-surfaces. Key parameters, including surface roughness, Shore A hardness, interfacial adhesion, static and dynamic friction coefficients, and material wear patterns, were analyzed. The mechanical properties of each rubber compound were characterized through Shore A hardness testing and ball indentation-retraction tests, measuring indentation force, energy, and adhesive properties. Sliding friction tests, simulating real climbing conditions, were conducted to understand the tribological behavior of each rubber compound under different loads, further analyzing static and dynamic friction coefficients and wear characteristics. The findings of this study indicate that rubber performance is a convolution of several factors, including material hardness, surface roughness, and interfacial adhesion. Contrary to popular belief, softer rubbers did not consistently exhibit superior tribological characteristics. The findings of this study suggest that climbing shoe selection and design should consider a broader range of material characteristics beyond hardness, emphasizing the role of surface roughness and adhesion in determining overall frictional performance. This research offers valuable insights for the climbing community, providing methodologies to benchmark climbing rubber material characteristics.